Analisis Pengaruh Investasi, Unit Usaha, dan Tenaga Kerja Terhadap PDRB Sektor Industri Pengolahan di Provinsi Jambi - Agus Ropik; Yulmardi Yulmardi; Jaya Kusuma Edi (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2017)
The study aims to analyze: (1) to know the development of investment, the number of business units, labor and manufacturing industry sector Jambi Province; and (2) to analyze the influence of investment, the number of business units, and labor to the processing industry sector of Jambi Province. The data used in this study is secondary data sourced from the Central Bureau of Statistics and BAPPEDA Jambi Province. For data analysis tool use path analysis. Based on the analysis result, it is known that: (1) simultaneously investment, the number of business unit and labor of processing industry sector have a significant effect to GDRP of processing industry sector of Jambi Province; (2) while partially variable having significant effect to GDRP of processing industry sector is investment variable of processing industry sector.